Anti-inflammatory effects of novel curcumin analogs in experimental acute lung injury. Issue 1 (December 2015) - Zhang, Yali; Liang, Dandan; Dong, Lili; Ge, Xiangting; Xu, Fengli; Chen, Wenbo; Dai, Yuanrong; Li, Huameng; Zou, Peng; Yang, Shulin; Liang, Guang
Abstract Background Acute lung injury (ALI) and its most severe form acute respiratory distress syndrome (ARDS) have been the leading cause of morbidity and mortality in intensive care units (ICU). Currently, there is no effective pharmacological treatment for acute lung injury. Curcumin, extracted from turmeric, exhibits broad anti-inflammatory properties through down-regulating inflammatory cytokines. However, the instability of curcumin limits its clinical application. Methods A series of new curcumin analogs were synthesized and screened for their inhibitory effects on the production of TNF-α and IL-6 in mouse peritoneal macrophages by ELISA. The evaluation of stability and mechanism of active compounds was determined using UV-assay and Western Blot, respectively.In vivo, SD rats were pretreatment withc26 for seven days and then intratracheally injected with LPS to induce ALI. Pulmonary edema, protein concentration in BALF, injury of lung tissue, inflammatory cytokines in serum and BALF, inflammatory cell infiltration, inflammatory cytokines mRNA expression, and MAPKs phosphorylation were analyzed. We also measured the inflammatory gene expression in human pulmonary epithelial cells. Results In the study, we synthesized 30 curcumin analogs. The bioscreeening assay showed that most compounds inhibited LPS-induced production of TNF-α and IL-6. The active compounds, a17, a18, c9 andc26, exhibited their anti-inflammatory activity in a dose-dependent manner and exhibited greater stability than curcuminin vitro . Furthermore, the active compoundc26 dose-dependently inhibited ERK phosphorylation.In vivo, LPS significantly increased protein concentration and number of inflammatory cells in BALF, pulmonary edema, pathological changes of lung tissue, inflammatory cytokines in serum and BALF, macrophage infiltration, inflammatory gene expression, and MAPKs phosphorylation. However, pretreatment withc26 attenuated the LPS induced increase through ERK pathwayin vivo. Meanwhile, compoundc26 reduced the LPS-induced inflammatory gene expression in human pulmonary epithelial cells. Conclusions These results suggest that the novel curcumin analogc26 has remarkable protective effects on LPS-induced ALI in rat. These effects may be related to its ability to suppress production of inflammatory cytokines through ERK pathway. Compoundc26, with improved chemical stability and bioactivity, may have the potential to be further developed into an anti-inflammatory candidate for the prevention and treatment of ALI.